Importance of social skills in Korea's labor market - CHOI, Jung Hee (KDI School, 2016)
According to the OECD’s project on Definition and Selection of Key Competencies, key competencies required for successfully dealing with the complex demands of society in the 21stCentury include “social skills”, or the ability to interact with other people. Although evidence from numerous researches emphasizes the importance of social skills, Korea’s education has continuously maintained its focus on rote-learning and cognitive skills. The aim of this research is to test whether social skills indeed have relevance in Korea’s labor market. Using data from Korea Education and Employment Panel, this study shows that social skills have apositiveimpact on individual earnings.Such a relationship between social skills and earnings holdstrue even after controlling for cognitive skills and other types of non-cognitive skills, as well as occupation and industry fixed effects.
Thesis(Master) --KDI School:Master of Development Policy,2016